IMPLEMENTING PROBLEM BASED LEARNING ASSISTED BY STUDENTS’ WORKSHEET AT SMA NEGERI 12 PEKANBARU - Armis Armis (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
This research was classroom action research aiming to analyze the implementation of Problem Based Learning assisted by Students' Worksheet at grade XI IPA.3 SMA Negeri 12 Pekanbaru. There were five variables investigated in this study, namely (1) learning management, (2) learning process, (3) students’ behavior, (4) students’ response, and (5) students’ achievement. The subjects of this study were 33 students at grade XI IPA.3 SMA Negeri 12 Pekanbaru. Data were collected through (1) observing the learning management, learning process, and students’ behavior, (2) filling in students’ response questionnaires (Likert Scale 1,2,3,4), and (3) examining mathematics achievement (scale 0-100). Data related to learning management, learning process, students’ behavior, and students’ response were analyzed by using quantitative descriptive analysis while data of students’ achievement were analyzed by using averages. Based on data analysis, it was revealed that learning management, learning process, students’ behavior, and students’ response were excellent. The students’ achievement before the treatement were not good but it increased after the treatment to be excellent for the material of linear form of trigonometric equation and to be good for squared form of trigonometric equation material. It could be concluded that the learning process was very good and students' achievement increased significantly after the treatment.